Closed form solutions of heat and mass transfer in the flow of a MHD visco-elastic fluid over a porous stretching sheet - Ashokkunar, K.; Veena, P.H.; Pravin, V.K. (Zielona Góra: Uniwersytet Zielonogórski)
The problem of heat and mass transfer in a visco-elastic fluid flow over a stretching sheet in the presence of a uniform magnetic field is examined. The important physical quantities such as the skin friction co-efficient, heat transfer co-efficient and the mass transfer co-efficient are determined. It is found that the heat and mass transfer distribution decreases with the increasing values of the visco-elastic parameter k1.
Keywords: heat transfer; mass transfer; MHD flow; porous stretching sheet; visco-elastic fluid